“The Revolution Will Be Feminist—Or It Won’t Be a Revolution”: Feminist Response to Inequality in Chile - Perry, Sarah (2022)
This article argues that gender inequality, which in Chile is superimposed on a societal and economic structure characterized by deep inequalities that cut across every aspect of society, has been sustained by a political and legal system that has severely limited women’s access to economic power and equality. The neoliberal policies implemented by the Pinochet dictatorship and maintained by the democratically elected regimes after 1990—generally characterized as an elitist democracy—have sustained this pattern of inequality. We argue that this gender inequality gave urgency to the regeneration and evolution of Chile’s feminist movement and drove the movement to develop claims against “the precarity of life,” uniting Chileans in a common struggle, contributing to the October 2019 “social explosion” and now the writing of a new constitution. We believe the current climate is rooted in the social mobilization that was the response to Chile’s economic and political system, and the feminist movement’s ability to put the rights of women at the forefront of the political and socio‐economic agenda. In conclusion, we reevaluate the current climate to consider what a significant feminist presence means and how women can be effectively included and benefit from Chile’s economy and influence its progress.